314 Patients with ovarian clear cell carcinoma are at high risk of secondary malignancy. (18th September 2019) - Nguyen, JMV; Vicus, D; Bernardini, MQ; Hogen, L
Abstract : Objectives: Ovarian clear cell carcinoma (OCCC) has unique clinical and molecular features compared to other epithelial ovarian cancer histologies. Our objective was to describe the incidence of secondary malignancies (SM) in patients with OCCC. Methods: Retrospective cohort study of patients with pure OCCC at two tertiary academic centres in Toronto, Canada between 1995–2017. Demographic and histopathologic details were obtained from chart review and confirmed with a provincial cancer registry. Results: Of 209 patients with OCCC, 53 developed a SM (25.4%), of whom 7 developed 2 SM. SM included: breast (13), skin (10), gastrointestinal tract (9), other gynecologic malignancies (8), thyroid (6), lymphoma (5), head and neck (4), urologic (3) and lung malignancies. Thirty-five SM occurred before index OCCC (median 9.4 years before), 21 after OCCC (median 5.8 years after), and 4 were diagnosed concurrently. More patients with SM had a smoking history that those without SM (28.3% vs 11.5%, p=0.004). Other demographic characteristics were similar between groups (age (56 vs 54, p=0.23), body mass index (25.7 vs 25.5, p=0.70), diabetes (5.7% vs 5.8%, p=0.76), proportion of patients of Asian ethnicity (18.9% vs 23.1%, p=0.66)). The proportion presenting with stage I OCCC was comparable (66% vs 59%, p=0.46). Only one patient had documented Lynch syndrome. Survival analysis is pending. Conclusions: Patients with OCCC are at increased risk of SM, most frequently non-Lynch syndrome related. This could suggest that a subset of patients with OCCC harbor mutations rendering them susceptible to SM. SM that could be associated with Lynch syndrome warrants genetic testing.